Modulation of magnetic damping constant of Fe2Co films by heavy doping of rare-earth Yb. (27th February 2017) - Wu, Kai; Tang, Minghong; Li, Dong; Guo, Xiaobin; Cui, Baoshan; Yun, Jijun; Zuo, Yalu; Xi, L; Zhang, Z Z
Abstract: The effect of rare-earth element Yb doping on modulating the magnetic properties, especially the damping constant, is investigated in a series of amorphous (Fe2 Co)(1− x ) Yb x thin films by the time-resolved magneto-optical Kerr effect at room temperature. A linear decrease of the saturation magnetization and in-plane uniaxial anisotropy field with the increase of x was observed and explained by the diluted effect of non-magnetic Yb doping. The magnetic damping constant performs a remarkable increase with Yb concentration. X-ray photoelectron spectroscopy reveals partial oxidation of Yb, which has large orbital moment and the associated large spin–orbital coupling (SOC) strength and may be responsible for the increased damping constant in contrast with the expected weak SOC and associated low damping constant of metallic Yb doping.